2014
DOI: 10.1080/09512748.2014.948569
|View full text |Cite
|
Sign up to set email alerts
|

The euro for China: too important to fail and too difficult to rescue

Abstract: The aim of this paper is to analyze China's strategy in relation to the euro. The first section summarizes China's active support to the single currency since its creation up to the first phase of the current Eurozone debt crisis. It shows how China has used a two-pronged approach. It has developed a public campaign in favor of the euro, especially when the market sentiment has been bearish on the single currency, and it has continued to be an active player in the European sovereign debt markets. The second pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A research by Otero-Iglesias demonstrated that China provided 'unequivocal support for the euro' in 2010 and 2011 and increased its holdings of debt from Italy, Spain, Ireland, Portugal and Greece. China's support for the Euro was mainly out of the following considerations: diversification of its foreign reserves; preserving the value of euro-denominated debt; helping maintain a dynamic European market which is important for Chinese imports and exports (Otero-Iglesias, 2014). With its financial support to the Euro, China also sought to get compromise from the EU, who may lift the arms embargo and grant market economy status to China.…”
Section: Eu-china Relations Revisitedmentioning
confidence: 99%
See 1 more Smart Citation
“…A research by Otero-Iglesias demonstrated that China provided 'unequivocal support for the euro' in 2010 and 2011 and increased its holdings of debt from Italy, Spain, Ireland, Portugal and Greece. China's support for the Euro was mainly out of the following considerations: diversification of its foreign reserves; preserving the value of euro-denominated debt; helping maintain a dynamic European market which is important for Chinese imports and exports (Otero-Iglesias, 2014). With its financial support to the Euro, China also sought to get compromise from the EU, who may lift the arms embargo and grant market economy status to China.…”
Section: Eu-china Relations Revisitedmentioning
confidence: 99%
“…With its financial support to the Euro, China also sought to get compromise from the EU, who may lift the arms embargo and grant market economy status to China. But the EU 'underappreciated China's help' (Otero-Iglesias, 2014). At the EU-China summit in 2012, former Chinese Premier Wen Jiabao openly expressed his disappointment: 'I have to be very frank in saying this.…”
Section: Eu-china Relations Revisitedmentioning
confidence: 99%